2020
DOI: 10.5194/acp-2020-529
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of the actual weather situation on non-CO<sub>2</sub> aviation climate effects: The REACT4C Climate Change Functions

Abstract: Abstract. Emissions of aviation include CO2, H2O, NOx, sulfur oxides and soot. Many studies have investigated the annual mean climate impact of aviation emissions. While CO2 has a long atmospheric residence time and is almost uniformly distributed in the atmosphere, non-CO2 gases, particles and their products have short atmospheric residence times and are heterogeneously distributed. The climate impact of non-CO2 aviation emissions is known to vary with different meteorological background situations. The aim o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Climate change functions (CCFs) allow for quantifying the global climate impact of local aircraft emissions as a function of emission location and time [7,13]. The aCCFs consider both CO2 and non-CO2 effects and measure global climate impact using the average temperature response integrated over a time period of 20 years (ATR20).…”
Section: Algorithmic Climate Change Functionsmentioning
confidence: 99%
“…Climate change functions (CCFs) allow for quantifying the global climate impact of local aircraft emissions as a function of emission location and time [7,13]. The aCCFs consider both CO2 and non-CO2 effects and measure global climate impact using the average temperature response integrated over a time period of 20 years (ATR20).…”
Section: Algorithmic Climate Change Functionsmentioning
confidence: 99%
“…Köhler et al (2008) identified that the emission altitude strongly influences the resulting climate impact, which is generally larger for emissions at high altitudes. Frömming et al (2012) demonstrated that the overall climate impact can be reduced by adapting flight altitudes, suggesting a possible mitigation strategy. The season in which the emission occurs also influences the resulting climate impact.…”
Section: Introductionmentioning
confidence: 99%
“…The non-CO2 effects include ozone (O3) formation and methane (CH4) depletion (causing the primary mode ozone (PMO) and stratospheric water vapour (SWV) decrease) due to aviation NOx emissions (Stevenson et al, 2004;Köhler et al, 2013;Myhre et al, 2007), contrail-cirrus (Heymsfield et al, 2010;Burkhardt and Kärcher, 2011;Schumann and Graf, 2013;Kärcher, 2018) and their alterations by aerosols direct and indirect effects (Kärcher et al, 2007;Penner et al, 2009;Myhre et al, 2013;Chen and Gettelman, 2016), and water vapour (H2O) effect (Wilcox et al, 2012). The non-CO2 effects depend not only on the emission quantity but also on the altitude, geographical location, time, and local weather conditions (e.g., Frömming et al, 2021). Therefore, it is possible to mitigate aviation's climate impact via operational measures to avoid climate-sensitive regions associated with non-CO2 effects (Grewe et al, 2017b;Sridhar et al, 2011;Yin et al, 2018;Matthes et al, 2020).…”
mentioning
confidence: 99%
“…The CCFs are 5D datasets (including longitude, latitude, altitude, time, and emission type) that describe the specific climate impacts, i.e., the average temperature change in K per flown kilometre or per emitted mass of the relevant species (NOx and H2O) locally. The high fidelity CCFs were computed for eight representative weather situations (five winter patterns and three summer patterns classified by Irvine et al (2013)) for the North Atlantic region (Frömming et al, 2021;Grewe et al, 2014a). Grewe et al (2014a) discussed the development and verification procedure of CCFs thoroughly.…”
mentioning
confidence: 99%